Controls on nitrite oxidation in the upper Southern Ocean: insights from winter kinetics experiments in the Indian sector - Mhlangabezi Mdutyana; Tanya Marshall; Xin Sun; Jessica Burger; Sandy Thomalla; Bess Ward; Sarah Fawcett (Zenodo, 2022)
This is a dataset to the paper "Controls on nitrite oxidation in the upper Southern Ocean: insights from winter kinetics experiments in the Indian sector" published under the Biogeosciencesjournal. This dataset contains rates of nitrite oxidation, kinetic parameters (half-saturation constant and maximum oxidation rate) for nitrite oxidation, latitudinal gradient of surface nitrite concentrations, integrated rates of ammonium and nitrite oxidation.